Peningkatan Motivasi Belajar Siswa Melalui Game Edukasi Woyground Pada Mata Pelajaran Matematika Kelas IX MTs Negeri 1 Probolinggo - Diana Putri; Moh Syadidul Itqon; Babun (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve the learning motivation of ninth-grade students of MTs Negeri 1 Probolinggo in Mathematics through the use of Woyground educational game media. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the study were 35 ninth-grade students of MTs Negeri 1 Probolinggo in the odd semester of the 2025/2026 academic year. Data collection was carried out through observation, learning motivation questionnaires, and learning outcome tests. Data were analyzed by calculating the percentage increase in learning motivation based on the formula proposed by Yonny et al. The results showed that the use of Woyground educational games can significantly increase student learning motivation. In the initial conditions, the average student learning motivation was 49% (moderate category). After the action in cycle I, learning motivation increased to 65% (high category), and in cycle II it increased again to 77.14% (very high category). Furthermore, increased learning motivation also impacted student learning outcomes, with completion rates increasing from 8.51% in the initial phase to 45.71% in Cycle I and 88.57% in Cycle II. This demonstrates that the implementation of the Woyground educational game media can create an engaging, interactive, and enjoyable learning environment, thereby enhancing student motivation and learning outcomes in Mathematics.